Dynamics of a diffusive vaccination model with nonlinear incidence. (15th June 2018) - Yang, Yu; Zhang, Shengliang
Abstract: A recent paper Xu et al. (2018) studied the global stability and traveling wave solution of a vaccination model with nonlinear incidence. Furthermore, in this paper, we first study the local stability of this model, and then establish the uniform persistence result. Our results are a supplement to above paper.